Anesthesia Management of a Patient with Idiopathic Thrombocytopenic Purpura Undergoing Laparoscopic Esophageal Hiatal Hernia Surgery: A Case Report - Zoukou Marie France Dominique Seri; Ahmed Uslu; Nedim Çekmen (Bali Journal of Anesthesiology)
Perioperative management of patients with immune thrombocytopenic purpura (ITP) has significant challenges for anesthesiologists. Perioperative bleeding due to thrombocytopenia in patients with ITP can be an essential challenge and is the most significant risk to anesthetists. Laparoscopic surgery can also be an additional challenge in such patients because of the risk of pneumoperitoneum that can lead to hemodynamic instability and bleeding deterioration. We present a 77-year-old successful anesthesia management of a female patient with ITP who underwent elective laparoscopic esophageal hiatal hernia surgery. A multidisciplinary team approach and comprehensive perioperative assessment and treatment are critical to ensure successful perioperative management of patients with ITP. We also aim to suggest that intravenous immunoglobulins therapy is not always mandatory in perioperative management of patients with ITP.